3D ELECTRON MICROSCOPY TOMOGRAPHY TO ASSESS MITOCHONDRIAL MORPHOLOGY IN THE ADULT HEART. (21st November 2014) - Kalkhoran, S; Hall, AR; Cole, A; White, I; Yellon, DM; Hausenloy, DJ
Abstract : Rationale: Modulating mitochondrial morphology may alleviate cardiac disease by preventing mitochondrial dysfunction. Mitofusin-2 (Mfn2) tethers junctional sarcoplasmic reticulum (jSR) to mitochondria. Standard 2D electron microscopy (2D-EM) does not allow the accurate assessment of mitochondrial morphology and jSR in the adult heart. Here, we investigate whether 3D-EM tomography, which allows one to image the mitochondria and jSR in 3-dimensions, can provide a more objective and accurate assessment of these features. Methodology: Electron micrographs of serially sectioned samples, obtained from left ventricular tissue harvested from either 8 week-old wild-type (WT) and Mfn2−/− mice, were imaged using either standard 2D-EM or 3D-EM tomography. Specific regions containing juxtaposed mitochondria and jSR were aligned, segmented, and reconstructed in 3D using Amira V.5. Results: In 2D-EM the Mfn2−/− mitochondria appeared to be larger, whereas in 3D-EM tomography the mitochondria appeared to be either similar or smaller in size, when compared to WT. Measuring the distance between mitochondria and jSR using 2D-EM gave highly variable results. However, 3D-EM allowed one to reconstruct the space between the juxtaposed organelles in 3D allowing a more accurate measurement of this distance. Conclusions: Here, we show that 3D-EM tomography is superior to 2D-EM in the assessment of mitochondrial morphology and can be used to more accurately measure the distance between mitochondrial and jSR in the adult heart. 3D-EM tomography will enable one to accurately assess mitochondrial morphology in different cardiac diseases (acute IRI, heart failure, LVH) and in the presence of co-morbidities (diabetes, metabolic syndrome, age).